From Play to Learning: Mobile Game Design to Improve Arabic Vocabulary in Junior High School: من اللعب إلى التعلم: تصميم الألعاب التعليمية المحمولة لتنمية المفردات العربية لدى تلاميذ المدرسة المتوسطة - Nur Afifatul Golimah; Kholisin; Nurhidayati (LISANIA: Journal of Arabic Education and Literature, 2025)
This study aims to 1) develop mobile game-based learning media as an innovative solution in improving students' vocabulary mastery at Junior High School 1 Lumajang, and 2) determine the feasibility and effectiveness of the product development. This research employs the Research and Development (R&D) method, utilizing the 4D model, which involves defining, designing, developing, and disseminating. The results showed that the mobile game-based learning media, Al-Mahiroh, was designed interactively and aligned with the curriculum, featuring main components such as vocabulary exercises, sentence structures, and dialogues presented through gamification. Media validation by experts scored 92% for material aspects and 97% for media aspects, indicating that it was deemed very feasible. The implementation of this media shows a significant increase in students' vocabulary ability, as evidenced by the results of the paired sample t-test, which produced a Significant Result. (2-tailed) of 0.000. The average posttest score of students increased from 30.90 to 79.90, indicating that the media was effective in improving students' vocabulary acquisition.